Clinical and microbiological performance of resin-modified glass-ionomer liners after incomplete dentine caries removal - Duque, Cristiane [UNESP]; Negrini, Thais de Cassia [UNESP]; Sacono, Nancy Tomoko [UNESP]; Palomari Spolidorio, Denise Madalena [UNESP]; de Souza Costa, Carlos Alberto [UNESP]; Hebling, Josimeri [UNESP] (Springer Heidelberg, 2009)
The aims of this study were to evaluate clinically and microbiologically the effects of two resin-modified glass-ionomer cements (RMGICs) used as liners after incomplete dentine caries removal and to identify Streptococcus mutans and Streptococcus sobrinus strains isolated from dentine samples, before and after indirect pulp treatment. Twenty-seven primary molars with deep carious lesions, but without signs and symptoms of irreversible pulpitis, were submitted to indirect pulp treatment. Treatment consisted of incomplete excavation of the carious dentine, application of one of the RMGICs (Vitrebond or Fuji Lining LC) or calcium hydroxide cement (Dycal), and sealing for 3 months. Clinical evaluation (consistency, color, and wetness of dentine) and carious dentine collects were performed before temporary sealing and after the experimental period. Microbiological samples were cultivated in specific media for subsequent counting of mutans streptococci (MS) and lactobacilli (LB). MS colonies were selected for identification of S. mutans and S. sobrinus by polymerase chain reaction. After 3 months, the remaining dentine was hard and dry, and there was a significant decrease in the number of MS and LB, in all groups, although complete elimination was not achieved in 33% and 26% of the teeth for MS and LB, respectively. From 243 MS colonies selected, 216 (88.9%) were identified as S. mutans and only 2 (0.8%) as S. sobrinus. The use of resin-modified glass-ionomer liners after incomplete caries removal, as well as a calcium hydroxide cement, promoted significant reduction of the viable residual cariogenic bacteria in addition to favorable clinical changes in the remaining carious dentine.
Keywords: Dental caries; Indirect pulp treatment; Glass-ionomer cements; Liners; Streptococcus mutans; Polymerase chain reaction